PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK. CABANG MANADO - Nelwan, Diandra Gabriela; Areros, William Agustinus; Tampi, Johny Revo Elia (Sam Ratulangi University, 2016)
Abstract, PT. Bank Negara Indonesia (Persero), Tbk Branch Manado is one of the largest national banks in North Sulawesi and even Indonesia. For the PT. BNI (Persero) Tbk branch Manado viewed with keen market in Indonesia such as in the area of Manado one with a marketing strategy, especially the quality of services in order to achieve company goals. This became the basis for the author to raise the issue: